Diffusible and Volatile Antifungal Compounds Produced by an Antagonistic Bacillus velezensis G341 against Various Phytopathogenic Fungi - Lim, Seong Mi; Yoon, Mi-Young; Choi, Gyung Ja; Choi, Yong Ho; Jang, Kyoung Soo; Shin, Teak Soo; Park, Hae Woong; Yu, Nan Hee; Kim, Young Ho; Kim, Jin-Cheol (The plant pathology journal, 2017)
The aim of this study was to identify volatile and agar-diffusible antifungal metabolites produced by sp. G341 with strong antifungal activity against various phytopathogenic fungi. Strain G341 isolated from four-year-old roots of Korean ginseng with rot symptoms was identified as based on 16S rDNA and sequences. Strain G341 inhibited mycelial growth of all phytopathogenic fungi tested. experiment results revealed that -butanol extract of fermentation broth effectively controlled the development of rice sheath blight, tomato gray mold, tomato late blight, wheat leaf rust, barley powdery mildew, and red pepper anthracnose. Two antifungal compounds were isolated from strain G341 and identified as bacillomycin L and fengycin A by MS/MS analysis. Moreover, volatile compounds emitted from strain G341 were found to be able to inhibit mycelial growth of various phytopathogenic fungi. Based on volatile compound profiles of strain G341 obtained through headspace collection and analysis on GC-MS, dimethylsulfoxide, 1-butanol, and 3-hydroxy-2-butanone (acetoin) were identified. Taken together, these results suggest that G341 can be used as a biocontrol agent for various plant diseases caused by phytopathogenic fungi.